The Promises and Challenges of the Use of Genomics in the Prescription of Exercise in Hypertension - Pescatello, Linda S. (Current Hypertension Reviews, 2010)
Hypertension is a major global public health problem. Exercise decreases blood pressure (BP) 5-7 mmHg among those with hypertension. Thus, exercise is recommended to prevent, treat, and control hypertension with a generic “one size fits all” approach. Yet, there is considerable individual variability in the BP response to exercise due to genetic and environmental factors that are not well understood. There is a significant genetic component to the BP response to exercise with heritability estimates of approximately 45% to 55%. Yet, identification of specific genetic variants accounting for this variability has proven to be a more challenging task than originally envisioned. This review describes work from our laboratory and others on candidate gene and BP association studies and how they account for some of the variability in the BP response to exercise. The ultimate goal of this work is to use genetic information to personalize exercise prescriptions to optimize the effectiveness of exercise as a therapeutic modality for the prevention, treatment, and control of hypertension. However, because of the complexities surrounding work in exercise genomics the future use of genomics in exercise prescription for hypertension is a vision of the future rather than a reality of the present.
Keywords: pre-hypertension